From "Spaces of Fear" to "Fearscapes": Mapping for Reframing Theories About the Spatialization of Fear in Urban Space. (August 2015) - Tulumello, Simone
The article engages with theory about the processes of spatialization of fear in contemporary Western urban space (fortification, privatization, exclusion/seclusion, fragmentation, polarization) and their relation to fear of crime and violence. A threefold taxonomy is outlined (Enclosure, Post-Public Space, Barrier), and "spaces of fear" in the city of Palermo are mapped with the aim of exploring the cumulative large-scale effects of the spatialization of fear on a concrete urban territory. Building on empirical evidence, the author suggests that mainstream theories be reframed as part of a less hegemonic and more discursive approach and that theories mainly based on the analyses of global cities be deprovincialized. The author argues for the deconstruction of the concept of "spaces of fear" in favor of the more discursive concept of "fearscapes" to describe the growing landscapes of fear in contemporary Western cities.